2020
DOI: 10.1002/iub.2343
|View full text |Cite
|
Sign up to set email alerts
|

Half a century of bacteriophage lambda recombinase: In vitro studies of lambda exonuclease and Red‐beta annealase

Abstract: DNA recombination, replication, and repair are intrinsically interconnected processes. From viruses to humans, they are ubiquitous and essential to all life on Earth. Single‐strand annealing homologous DNA recombination is a major mechanism for the repair of double‐stranded DNA breaks. An exonuclease and an annealase work in tandem, forming a complex known as a two‐component recombinase. Redβ annealase and λ‐exonuclease from phage lambda form the archetypal two‐component recombinase complex. In this short revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The homo-oligomerization of Redβ has been reported by several groups using various approaches and techniques, including native mass spectrometry ( 27 ), electron microscopy ( 25, 59 ) and atomic force microscopy ( 11, 26 ). These results are briefly summarized above and in more detail in our recent review ( 16 ). Our reconstruction shows how Redβ 177 oligomerizes with substantial contacts between adjacent subunits in the helix, but there is limited top-bottom contacts between corresponding monomers in the next turn of the helix (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The homo-oligomerization of Redβ has been reported by several groups using various approaches and techniques, including native mass spectrometry ( 27 ), electron microscopy ( 25, 59 ) and atomic force microscopy ( 11, 26 ). These results are briefly summarized above and in more detail in our recent review ( 16 ). Our reconstruction shows how Redβ 177 oligomerizes with substantial contacts between adjacent subunits in the helix, but there is limited top-bottom contacts between corresponding monomers in the next turn of the helix (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…It has also emerged as a tool for genetic manipulation, termed recombineering ( 14, 15 ). There are currently two proposed models for how SSA may occur, which have been recently reviewed by us ( 16 ) and others ( 1, 17 ). In brief, variable processing of dsDNA ends by λExo leads to two different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Although some viruses with small circular genomes, such as the papovaviruses, have evolved to utilize host DNA replication machinery to replicate their genomes [ 17 ], larger DNA viruses have evolved to Recombination-Dependent Replication (RDR) during genome replication using virally encoded recombinases [ 5 ]. The best-characterized example of an exo/SSAP complex is phage λ Redα/β, which in addition to its role in viral replication, has been used to promote in vivo recombination-mediated genetic engineering or recombineering [ 2 , 18 , 19 ]. Interestingly, herpes simplex virus (HSV) also encodes an exo/SSAP comprised of the 5′-to-3′ alkaline exonuclease (UL12) and an ssDNA annealing protein (ICP8), and our laboratory has shown that both activities are essential for HSV DNA replication and the formation of replication compartments [ 4 , 6 , 20 , 21 ].…”
Section: General Mechanism Of Recombinationmentioning
confidence: 99%
“…Extensive research on the mechanisms of recombination in both prokaryotic and eukaryotic cellular organisms has revealed a complex set of pathways by which genetic information is exchanged and repaired. Given the importance of these processes, it is perhaps not surprising that viruses have also evolved to rely heavily on recombination for genome replication and repair and to promote viral diversity [ 1 , 2 , 3 , 4 , 5 , 6 ]. Although most DNA and RNA viruses utilize recombination during replication, in this paper, we focus on Herpes and Coronaviruses, as these two viruses, in particular, have evolved efficient recombination pathways that specifically utilize virally encoded exonucleases.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, λ exonuclease treatment is used to convert dsDNA to a more accessible ssDNA analyte. 11 Avoiding these stages is desirable both for fast, low temperature, and low-cost POC diagnostics as well as for the analysis of RNA under native conditions, e.g. , RNA monitoring in live cells.…”
mentioning
confidence: 99%